Boundary layer flow and heat transfer past a permeable shrinking surface embedded in a porous medium with a second-order slip: A stability analysis. (25th March 2017) - Mat Yasin, Mohd Hafizi; Ishak, Anuar; Pop, Ioan
Abstract: The fluid flow and heat transfer over a permeable shrinking sheet embedded in a porous medium with a second-order slip is studied. Using appropriate similarity variables, the governing partial differential equations are reduced to ordinary differential equations before being solved numerically by a shooting method for different values of the selected governing parameters. The numerical results reveal that two (dual) solutions are possible for a certain range of these parameters. A stability analysis is performed to determine which solution is stable and which one is not. The effects of suction and the second order slip parameters on the skin friction coefficient and the local Nusselt number as well as on the velocity and temperature profiles are plotted and discussed. It is found that applying the slip condition increases the range of solutions. Also, the skin friction coefficient is higher for the no slip condition compared to that of with slip condition.